Disrupted Daily Activities From Interruptive Smartphone Notifications: Relations With Depression and Anxiety Severity and the Mediating Role of Boredom Proneness. (February 2021) - Elhai, Jon D.; Rozgonjuk, Dmitri; Alghraibeh, Ahmad M.; Yang, Haibo
Little prior research on computer or smartphone interruptive notifications (INs) has examined psychological constructs associated with their adverse effects. We examined several mental health constructs in relation to disruptions in various daily activities resulting from INs. A total of 316 undergraduate students completed a web survey querying severity of depression, anxiety, boredom proneness, emotional distress tolerance, and frequency of IN-related activity disruptions. Bivariate correlations revealed that IN-related activity disruptions were positively related to levels of depression, anxiety, and boredom proneness. Using structural equation modeling, boredom proneness mediated relations between depression severity and IN-related disruptions. Results are discussed within the context of theories on cognitive resource limitations and excessive Internet use.